Scientific advice and administrative traditions: the role of chief ccientists in climate change adaptation - Schmidt, Nicole; Teschner, Na'ama; Negev, Maya (Review of policy research, 2018)
The role of the chief scientist (CS), a key administrative position in various Israeli ministries, is to fund policy-oriented research and support evidence-based decision-making. Has the CS's role promoted or constrained incorporation of scientific advice regarding climate change adaptation into governmental policy? Have administrative traditions affected the adaptation planning process in Israel? Analysis of documents and 26 in-depth interviews with key stakeholders sheds light on the ongoing climate change adaptation policy formulation process. Our study reveals that the CS of the Ministry of Environmental Protection functions as a bridge at different interfaces and can be characterized as a boundary worker between institutions. The inherent independence of this position facilitates the CS's ability to initiate, foster, and prioritize complex issues such as adaptation. Our findings further suggest that the perception that Israel has already adapted, or will easily adapt, has negatively affected the adaptation process.